IDENTIFIKASI BIAYA PENGENDALIAN HAMA DAN PENYAKIT PADA BEBERAPA TANAMAN HORTIKULTURA DI DESA PALELON KECAMATAN MODOINDING - Merifka Rahel Ratu; O. Esri H. Laoh; Paulus A. Pangemanan (Sam Ratulangi University, 2021)
The purpose of this study was to determine the cost of controlling pests and diseases in horticultural crops (potatoes, onions, cabbage) in Palelon Village, Modoinding District. This research was started from December 2019 to February 2020. The data used in this study are primary and secondary data. The method of selecting respondents was done purposively. Methods of data collection were conducted interviews guided by questionnaires that had been prepared beforehand. The method of data analysis in this study was analyzed descriptively which is presented to describe or describe the collected data using tables. Based on the results of the study it can be concluded that the highest control costs incurred by farmers are maintenance costs, then weeding / land processing, and control and seeding.